Marginal Integrity of Class-I Restorations, Restored with Amalgam and Bonded Amalgam; A Comparative Study - Tanweer Ahmed; Asad Mahmood; Nasir-Ud- Din; Helen Mary Robert; Rafia Mahmood; Usman Tahir Swati (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the marginal integrity of Class-I amalgam and bonded amalgam restorations in maxillary and mandibular molars at seven days, three, six and twelve-months intervals.